Electrical equipment motor controllers and operation - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
This interactive training unit is designed to familiarize trainees with basic concepts associated with what motor controllers do and how they do it. Typical steps for starting up, checking, and shutting down motors are also covered. After completing this unit, trainees should be able to explain how motor controllers control and protect motors. They should also be able to describe how to start up a motor, perform operating checks on a motor, and shut down a motor.
Keywords: Electric controllers; Electric motors -- Electronic control; Electric motors